(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In a typical cloud computing diverse facilitating components like hardware, software, firmware, networking, and services integrate to offer different computational facilities, while Internet or a private network (or VPN) provides the required backbone to deliver the services. The security risks to the cloud system delimit the benefits of cloud computing like “on-demand, customized resource availability and performance management”. It is understood that current IT and enterprise security solutions are not adequate to address the cloud security issues. This paper explores the challenges and issues of security concerns of cloud computing through different standard and novel solutions. We propose analysis and architecture for incorporating different security schemes, techniques and protocols for cloud computing, particularly in Infrastructure-as-a-Service (IaaS) and Platform-as-a-Service (PaaS) systems. The proposed architecture is generic in nature, not dependent on the type of cloud deployment, application agnostic and is not coupled with the underlying backbone. This would facilitate to manage the cloud system more effectively and provide the administrator to include the specific solution to counter the threat. We have also shown using experimental data how a cloud service provider can estimate the charging based on the security service it provides and security-related cost-benefit analysis can be estimated. Cloud computing security is an important aspect of quality of service from cloud service providers.Security concerns arise as soon as one begins to run applications beyond the designated firewall and move closer towards the public domain. In violation of security in any component in the cloud can be disaster for the organization (the customer) as well as for the provider. In this paper, we propose a cloud security model and security framework that identifies security challenges in cloud computing.